Narrowband Organic Light‐Emitting Diodes for Fluorescence Microscopy and Calcium Imaging. Issue 42 (5th September 2019) - Murawski, Caroline; Mischok, Andreas; Booth, Jonathan; Kumar, Jothi Dinesh; Archer, Emily; Tropf, Laura; Keum, Chang‐Min; Deng, Ya‐Li; Yoshida, Kou; Samuel, Ifor D. W.; Schubert, Marcel; Pulver, Stefan R.; et al.
Abstract: Fluorescence imaging is an indispensable tool in biology, with applications ranging from single‐cell to whole‐animal studies and with live mapping of neuronal activity currently receiving particular attention. To enable fluorescence imaging at cellular scale in freely moving animals, miniaturized microscopes and lensless imagers are developed that can be implanted in a minimally invasive fashion; but the rigidity, size, and potential toxicity of the involved light sources remain a challenge. Here, narrowband organic light‐emitting diodes (OLEDs) are developed and used for fluorescence imaging of live cells and for mapping of neuronal activity in Drosophila melanogaster via genetically encoded Ca 2+ indicators. In order to avoid spectral overlap with fluorescence from the sample, distributed Bragg reflectors are integrated onto the OLEDs to block their long‐wavelength emission tail, which enables an image contrast comparable to conventional, much bulkier mercury light sources. As OLEDs can be fabricated on mechanically flexible substrates and structured into arrays of cell‐sized pixels, this work opens a new pathway for the development of implantable light sources that enable functional imaging and sensing in freely moving animals. Abstract : Organic light‐emitting diodes (OLEDs) are used as light source for fluorescence microscopy. Spectral multiplexing enables high contrast and results in fluorescence images of live cells with similar image quality to conventional illumination. Furthermore, the device is applied to recording neuronal activity in small‐animal models at video rates.